A03 Protein localisation studies: where is huntingtin hiding?. (16th November 2010) - Hughes, A; Ersoy, N; Elliston, L; Jones, L
Abstract : Background: The underlying mutation of the neurodegenerative disorder Huntington's disease (HD) is an expanded and unstable CAG repeat in exon 1 of the HD gene. This is translated into an expanded polyglutamine tract at the N terminal of the gene product huntingtin (Htt). Htt has been suggested to have a role in subcellular transport and transcription but the precise function of the Htt protein remains elusive. Htt location and the characteristics of normal and mutant Htt in different subcellular locations and cell types remain unclear yet may give further clues to the normal and mutant functions of this protein. Aims: This study has investigated the subcellular localisation of both endogenous and overexpressed Htt in cells in culture and assessed the effects of epidermal growth factor (EGF) on this localisation. Methods: HeLa, HEK293, N2A, PC12 and IMR32 cells were grown in culture and studied by either light or confocal laser scanning microscopy. Overexpressed Htt was fluorescently tagged while antibodies spanning the entire length of the Htt protein were employed to detect the endogenous protein. Results: While overexpressed Htt remained exclusively cytoplasmic, endogenous Htt appeared to reside in both the nucleus and the cytoplasm of cells cultured under standard conditions. On addition of EGF, an apparent reduction in the nuclear pool of Htt was noted. Conclusions: These findings raise the possibility of growth factor mediated movement of the Htt protein from the nucleus to the cytoplasm or possibly growth factor mediated post-translational modification of Htt, rendering it less available for antibody detection. This paves the way for further studies investigating the role of growth factors in HD pathogenesis.